Knockout of miR-21-5p alleviates cartilage matrix degradation by targeting Gdf5 in temporomandibular joint osteoarthritis. Issue 10 (7th October 2020) - Zhang, Aobo; Ma, Shixing; Yuan, Lingyu; Wu, Shichao; Liu, Shaopeng; Wei, Xiang; Chen, Lei; Ma, Chuan; Zhao, Huaqiang
Abstract : Aims: The study aimed to determine whether the microRNA miR21-5p (MiR21) mediates temporomandibular joint osteoarthritis (TMJ-OA) by targeting growth differentiation factor 5 (Gdf5). Methods: TMJ-OA was induced in MiR21 knockout (KO) mice and wild-type (WT) mice by a unilateral anterior crossbite (UAC) procedure. Mouse tissues exhibited histopathological changes, as assessed by: Safranin O, toluidine blue, and immunohistochemistry staining; western blotting (WB); and quantitative real-time polymerase chain reaction (RT-qPCR). Mouse condylar chondrocytes were transfected with a series of MiR21 mimic, MiR21 inhibitor, Gdf5 siRNA (si-GDF5), and flag-GDF5 constructs. The effects of MiR-21 and Gdf5 on the expression of OA related molecules were evaluated by immunofluorescence, alcian blue staining, WB, and RT-qPCR. Results: UAC altered the histological structure and extracellular matrix content of cartilage in the temporomandibular joint (TMJ), and KO of MiR21 alleviated this effect (p < 0.05). Upregulation of MiR21 influenced the expression of TMJ-OA related molecules in mandibular condylar chondrocytes via targeting Gdf5 (p < 0.05). Gdf5 overexpression significantly decreased matrix metalloproteinase 13 (MMP13) expression (p < 0.05) and reversed the effects of MiR21 (p < 0.05). Conclusion: MiR21, which acts as a critical regulator of Gdf5 in chondrocytes, regulates TMJ-OA related molecules and is involved in cartilage matrix degradation, contributing to the progression of TMJ-OA. Cite this article: Bone Joint Res 2020;9(10):689–700.